A formação do professor e o desenvolvimento de competências pedagógico-digitais: experiência em escola pública que participa do Projeto UCA - Piorino, Gilda Inêz Pereira (2012)
This thesis shows that the training of teachers from a school that participates in the One Computer per Student UCA Project (Projeto Um Computador por Aluno Projeto UCA) allows the development of digital-pedagogical competencies. It also intends to provide the understanding of the concept of digital-pedagogical competencies, offering contributions to the development of theories which may deal with the levels that characterize the evolution process of the teacher s technological and pedagogical appropriation, considering other already existent theories that are related to the appropriation of technologies. For that, an investigation was carried out at the school EE Antonio Carlos Ferreira Nobre, São Paulo, whose teachers took part in the second phase of the UCA Project. This phase involves the implementation of educational laptops in public schools for the use of both students and teachers, and the training of teachers so they can use this technology and the infrastructure to access wireless Internet, bringing to the schools new concepts related to mobile technology. Pontific Catholic University of São Paulo (PUCSP Pontíficia Universidade Católica de São Paulo) was responsible for the teachers training. Considering the assumption that the laptop s pedagogical appropriation is connected to technological appropriation, in a competent and conscious way, the research s theory includes the concepts of technological appropriation, competencies, and consciousness. These are also used as categories for the study that aims to identify the teachers advances regarding the educational laptop pedagogical appropriation. There is also the assumption that the levels of the laptop s pedagogical appropriation are associated with these categories, to a lower or higher degree. The identification of the teachers technological and pedagogical difficulties during the training process that took place at the school EE Antonio Carlos Ferreira Nobre led the trainers to establish new strategies for the course s development. These included workshops regarding themes directly related to the teachers needs concerning the activities done with the laptop, so to increase these teachers consciousness level. The observations of the initial stages of the training process and of the workshops developed allowed for an understanding of the challenge faced by the teachers when they had to deal with this new technology, in addition to their difficulties, and the values and meanings attributed by these teachers. This knowledge guided the next steps in the training process so the teachers could appropriate the technologies, developing new and diverse competencies for the execution of their pedagogical practices. The identification of the teachers advances regarding the laptop s pedagogical and technological appropriation was analyzed based on the theories about appropriation development proposed by Sandholtz, Ringstaff and Dwyer (1997);on the studies by Borges (2009) regarding technological appropriation (emphasizing her conclusions about the impact caused by the emotional aspects on this appropriation s development); and on the digital competencies model created by Krumsvik (2008), which was produced with the intention of confirming the direct relation among the categories appropriation, consciousness and competencies. In order to enrich the reflection, a dialogue was created with theorists and specialists who emphasize the importance of the teacher s training occurring in a constructive and contextualized situation along with the consciousness of the people who took part in the project, such as Freire (1983), Valente (1999), Almeida (2004),and Prado (1996). The studies that were carried out by the PUCSP s team, who was responsible for the training, allowed the conclusion that the strategies added to the training s initial methodology permitted the teacher s grasping of consciousness and somehow the customization of the course according to the class s profile, respecting each teacher s way of learning. The technological and pedagogical appropriation of the laptop is currently in process, and tends to proceed since, as the course progresses, this has created opportunities for the teachers to reflect on the teaching and learning processes concerning the laptop and to develop new levels of competencies. At the end of the course, the PUCSP team introduced a support plan for the teacher that will allow the training process to continue. Even though the students were not the subjects of the research, the investigation also allowed the comparison between the students and the teacher s technological appropriation processes, permitting the observation of a digital gap between them which is becoming smaller as the teachers reach higher levels of technology pedagogical appropriation, developing the digital-pedagogical competency, whose concept was introduced and analyzed during this research